Kurikulum pendidik Rabbani untuk peningkatan kompetensi kepribadian guru - Arifin, Rizal (Tawazun: Jurnal Pendidikan Islam, 2022)
Rabbani educators are the best educator models according to the Qur'an. The presence of Rabbani educators is one of the main solutions to educational problems that have developed from the past until now. The most important educational problem is the quality of educators, with the assumption that the best curriculum is the teacher, the author views improving the quality of teachers or educators to be a very important and urgent agenda. Becoming a Rabbani educator requires good competencies that are interrelated between personality, social, pedagogical and professional competencies. In the book al-Fathu ar-Rabbí¢ni Wa al-Faydhu ar-Rahmí¢ny, Shaykh Abdul Qadir al-Jailany (561 H), a Hanbali scholar who is famous for his expertise in the field of Jurisprudence and purification of the heart, he explains the characteristics of the Rabbani personal figure who can applied by everyone with whatever profession they carry, including being an educator. The research in this thesis aims to determine the character of Rabbani educators and how to apply them as a simple curriculum at the Mahad Ihya As Sunnah School of Teacher (SOT) Tasikmalaya. The results of this study are expected to be a guide in development and training activities for educators in the Mahad Ihya As Sunnah environment starting from PAUD to high school. The research in this thesis uses qualitative research with library research and field research with a phenomenological approach. The research in this thesis is descriptive by taking the object of SOT Mahad Ihya As Sunnah Tasikmalaya. In collecting data, this study uses the method of observation, document review, interviews and documentation. For data analysis using induction analysis which is then described. The patterns used include: data collection, data reduction, data display and drawing conclusions. From the research, a simple curriculum can be made consisting of objectives, materials, methods and evaluations. The goal is to produce teacher educators with Rabbani character, competence, dedication and achievement. The materials prepared to achieve these goals consist of religious knowledge and general science related to the latest teaching and education. The method is designed with various learning methods and exercises such as lectures and exercises. Evaluation is carried out periodically with a special rubric which is carried out every semester by issuing a certificate or educator report card. Abstrak Pendidik Rabbí¢ni adalah model pendidik terbaik menurut Al-Qurí¢n. Kehadiran pendidik Rabbí¢ni menjadi salah solusi utama masalah-masalah pendidikan yang berkembang dari dulu hingga kini. Masalah pendidikan yang paling utama adalah kualitas pendidik, dengan asumsi bahwa kurikulum terbaik adalah guru, penulis memandang perbaikan kualitas guru atau pendidik menjadi agenda yang sangat penting dan mendesak. Menjadi sosok pendidik Rabbí¢ni diperlukan kompetensi yang baik yang saling terikat antara kompetensi kepribadian, sosial, pedagogi dan profesional. Dalam kitab al-Fathu ar-Rabbí¢ni Wa al-Faydhu ar-Rahmí¢ny, Syaikh Abdul Qadir al-Jailany (561 H), seorang ulama Hanbali yang terkenal kepakarannya dalam bidang Fikih dan pensucian hati, beliau menjelaskan karakter-karakter sosok pribadi Rabbí¢ni yang bisa diterapkan oleh semua orang dengan profesi apapun yang diembannya, termaasuk menjadi seorang pendidik. Penelitian dalam tesis ini bertujuan untuk mengetahui karakter pendidik Rabbí¢ni dan bagaimana aplikasinya sebagai sebuah kurikulum sederhana di School of Teacher (SOT) Mahad Ihya As Sunnah Tasikmalaya. Hasil penelitian ini diharapkan menjadi panduan dalam kegiatan pengembangan dan pelatihan bagi para pendidik di lingkungan Mahad Ihya As Sunnah mulai dari PAUD hingga SMA. Penelitian dalam tesis ini menggunakan penelitian kualitatif dengan metode studi pustaka (library research) dan studi lapangan (field research) dengan pendekatan phenomenologis. Penelitian dalam tesis ini bersifat deskriftif dengan mengambil objek SOT Mahad Ihya As Sunnah Tasikmalaya. Dalam pengumpulan data, penelitian ini menggunakan metode observasi, telaah dokumen, wawancara dan dokumentasi. Untuk analisis data menggunakan induksi analisis yang kemudian dideskripsikan. Pola yang digunakan meliputi : pengumpulan data, reduksi data, display data dan penarikan kesimpulan. Dari penelitian dapat dibuat kurikulum sederhana yang terdiri dari tujuan, materi, metode dan evaluasi. Tujuan mencetak pendidik guru yang berkarakter Rabbí¢ni, berkompeten, berdeikasi dan berprestasi. Materi yang disusun untuk meraih tujuan tersebut terdiri dari ilmu agama dan ilmu umum yang berkaitan dengan keguruan dan kependidikan yang mutakhir. Metode yang dirancang dengan berbagai metode pembelajaran dan Latihan seperti ceramah dan Latihan. Evaluasi dilakuakan secara berkala dengan rubrik yang khusu yang dilakuakan setiap semester dengan diterbitkan sertifikat atau raport pendidik.